Neutralization Activity of Standard and Hyperimmune Intravenous Immunoglobulins Against Recently Circulating SARS-CoV-2 Variants - Dongxiao Liu; Lorenza Bellusci; Hana Golding; Surender Khurana (Vaccines)
Our study demonstrates that IVIG lots manufactured in 2023–2024 contain neutralizing antibodies against circulating Omicron variants, including KP.3 and XEC. These variants are resistant to all convalescent plasma and IVIG preparations produced prior to 2023. Therefore, recent IVIG lots may provide some protection against COVID-19 caused by circulating SARS-CoV-2 variants.